Analisis Dampak Penambangan Pasir Pantai Terhadap Kerusakan Lingkungan Fisik di Kecamatan Morotai Selatan Kabupaten Pulau Morotai - Irfan Hi. Abd Rahman; Parto Sumktaki (Peneliti.net, 2020)
The environmental condition around the coastal area became damaged as a result of sand mining activities resulting in physical damage to the beach. The purpose of this study is to understand the impact of coastal sand miners on the physical environment in the coastal areas of South Morotai Sub-District. This research was carried out at locations affected by sand mining, namely the coastal areas of Momujiu Village and Sabatai South Morotai Sub-District, Morotai Island Regency. From the search results in the field, there are 13 garden landowners who are included in the coastal area that has been used as a sand mining site. The results showed that 71% of presentations had a physical environmental impact and 29% had no impact on the Physical environment. Thus, the impact of sand mining around the coast on the physical environment is very bad, including damage to coastal ecosystems as a result of the loss of coastal forests, damage to farm roads between farmers' land and coastal morotai south morotai regency morotai island regency.